Waarschijnlijk gemaakt door Gebr. van Oven vaandels te Den Haag. Zie voor uitgevoerd ontwerp L1/467
Waarschijnlijk gemaakt door Gebr. van Oven vaandels te Den Haag. Zie voor uitgevoerd ontwerp L1/467.